2012
DOI: 10.1093/pasj/64.5.109
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsic Short-Term Radio Variability Observed in PKS 1510−089

Abstract: We searched a short-term radio variability in an active galactic nucleus, PKS 1510 089. Daily flux monitoring for 143 d at 8.4 GHz was performed, and VLBI observations at 8.4, 22, and 43 GHz were carried out 4 times during the flux monitoring period. As a result, variability with a time scale of 20 to 30 d was detected. The variation patterns were very much alike at three frequencies; moreover, those at 22 and 43 GHz were synchronized. These properties support that this short-term variability is an intrinsic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The apparent speed in the ultrarelativistic jet of PKS 1510-089 has been observed to be upto 46c (Jorstad et al 2005) which suggests that the Doppler factor could be very high for this source. From equation ( 6) for t var = 1.30 hr, δ = 47 (Kadota et al 2012), we get an emission region of radius R ∼ 4.85 × 10 15 cm. A less extreme Doppler factor of 10 would imply an emission region of radius R ∼ 1.03 × 10 15 cm.…”
Section: Spectral Energy Distributions Of Flaresmentioning
confidence: 96%
“…The apparent speed in the ultrarelativistic jet of PKS 1510-089 has been observed to be upto 46c (Jorstad et al 2005) which suggests that the Doppler factor could be very high for this source. From equation ( 6) for t var = 1.30 hr, δ = 47 (Kadota et al 2012), we get an emission region of radius R ∼ 4.85 × 10 15 cm. A less extreme Doppler factor of 10 would imply an emission region of radius R ∼ 1.03 × 10 15 cm.…”
Section: Spectral Energy Distributions Of Flaresmentioning
confidence: 96%
“…We employed the 'Z-scan' method to remove both the gain and atmospheric fluctuations, and the pointing offsets. The detailed procedure of the observation and data reduction of the method is described by Kadota et al (2012). The flux density of 1H 0323+342 was measured by comparing the total received power with that of a strong, nearby radio source 3C 123 (9.310 Jy; Ott et al 1994).…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Agudo et al (2011 also suggested that the γ-ray emitting site is located at a distance > 14 pc from the central engine. The time scale of the radio flux variability seen in AGNs is often shorter than one month (Lazio et al, 2001;Kadota et al, 2012), and therefore it is important to carry out frequent VLBI monitoring observations on a time intervals of weeks.…”
Section: Introductionmentioning
confidence: 99%